2017
DOI: 10.1152/ajpheart.00728.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Med1 deletion promotes early lethality, cardiac remodeling, and transcriptional reprogramming

Abstract: The mediator complex, a multisubunit nuclear complex, plays an integral role in regulating gene expression by acting as a bridge between transcription factors and RNA polymerase II. Genetic deletion of mediator subunit 1 (Med1) results in embryonic lethality, due in large part to impaired cardiac development. We first established that Med1 is dynamically expressed in cardiac development and disease, with marked upregulation of Med1 in both human and murine failing hearts. To determine if Med1 deficiency protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…As Mediator function is closely associated with energy utilization and homeostasis (22,24,(39)(40)(41), it is not entirely unexpected that overexpression of Cdk8 results in a large enrichment of downregulated mitochondrial-based metabolic genes and pathways (Figures 6 and 7). In fact, we see considerable overlap between the RNA-seq results presented here (885 of 1,160 genes expressed >1.5-fold, r 2 = 0.61) and those from cardiac deletion of the core Mediator subunit Med1 (Med1cKO) that we recently reported (24). It is intriguing that 94% of the shared genes between presymptomatic Cdk8-transgenic and advanced dilated Med1cKO ventricles have the same directionality in terms of upregulation or downregulation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As Mediator function is closely associated with energy utilization and homeostasis (22,24,(39)(40)(41), it is not entirely unexpected that overexpression of Cdk8 results in a large enrichment of downregulated mitochondrial-based metabolic genes and pathways (Figures 6 and 7). In fact, we see considerable overlap between the RNA-seq results presented here (885 of 1,160 genes expressed >1.5-fold, r 2 = 0.61) and those from cardiac deletion of the core Mediator subunit Med1 (Med1cKO) that we recently reported (24). It is intriguing that 94% of the shared genes between presymptomatic Cdk8-transgenic and advanced dilated Med1cKO ventricles have the same directionality in terms of upregulation or downregulation.…”
Section: Discussionmentioning
confidence: 97%
“…This submodule regulates gene expression through its dynamic association with the Mediator core complex and through its Cdk8 activity (19)(20)(21). We recently reported the novel observation that cardiac Med13 functions to regulate whole-body energy homeostasis (22,23) and that Med1 is essential in postnatal and adult cardiomyocytes (24); however, the function of Mediator kinase activity has yet to be determined. Knockdown and overexpression studies in other systems have shown that Cdk8 can impart both activating and repressive effects on transcription in celland gene-specific contexts (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported by two independent groups that cardiac-specific deletion of Med1 leads to severe DCM and premature death in mice. Although many calcium-handling genes were downregulated in the Med1 -/-heart, they were measured after the onset of DCM, which has been associated with decreased calcium-handling gene expression, as discussed above (49,50).…”
Section: Egr1mentioning
confidence: 98%
“…Cardiac-specific deletion of Med1 in mice results in dilated cardiomyopathy, decreased cardiac function and lethality 59 . Mutations in Med23 and Med25 have been linked to congenital heart disease in clinical studies 60,61 . In addition, Med14 mutants give rise to heart defects in zebrafish 62 .…”
Section: Role Of the Mediator Complex In Cardiovascular Diseasementioning
confidence: 99%
“…Gene expression was analyzed using the ΔΔCT method and relative expression was normalized to Rpl7l1. Sequences for the primers are as listed in previous studies 60,65 .…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%